Growth hormone (GH) receptor (GHR)-specific inhibition of GH-Induced signaling by soluble IGF-1 receptor (sol IGF-1R). (15th July 2019) - Zhang, Yue; Gc, Sajina; Patel, Sweta B.; Liu, Ying; Paterson, Andrew J.; Kappes, John C.; Jiang, Jing; Frank, Stuart J.
Abstract: Human growth hormone (GH) binds and activates GH receptor (GHR) and prolactin (PRL) receptor (PRLR). LNCaP human prostate cancer cells express only GHR. A soluble fragment of IGF-1 receptor (IGF-1R) extracellular domain (sol IGF-1R) interacts with GHR and blocks GH signaling. We now explore sol IGF-1R's specificity for inhibiting GH signaling via GHR vs. PRLR and test GHR and PRLR extracellular domain inhibition determinants. Although T47D human breast cancer cells express GHR and PRLR, GH signaling is largely PRLR-mediated. In T47D, sol IGF-1R inhibited neither GH- nor PRL-induced STAT5 activation. However, sol IGF-1R inhibited GH-induced STAT5 activation in T47D-shPRLR cells, which harbor reduced PRLR. In MIN6 mouse β-cells, bovine GH (bGH) activates mouse GHR, not PRLR, while human GH activates mouse GHR and PRLR. In MIN6, sol IGF-1R inhibited bGH-induced STAT5 activation, but partially inhibited human GH-induced STAT5 activation. These findings suggest sol IGF-1R's inhibition is GHR-specific. Using a cellular reconstitution system, we compared effects of sol IGF-1R on signaling through GHR, PRLR, or chimeras in which extracellular subdomains 2 (S2) of the receptors were swapped. Sol IGF-1R inhibited GH-induced STAT5 activation in GHR-expressing, not PRLR-expressing cells, consistent with GHR specificity of sol IGF-1R. Interestingly, we found that GHR S2 (which harbors the GHR-GHR dimer interface) was required, but not sufficient for sol IGF-1R inhibition of GHR signaling. These results suggest sol IGF-1R specifically inhibits GH-induced GHR-mediated signaling, possibly through interaction with GHR S1 and S2 domains. Our findings have implications for GH antagonist development. Highlights: GHR signaling is augmented by association with IGF-1 receptor. A soluble IGF-1R fragment (sol IGF-1R) interacts with GHR and inhibits GH signaling. Sol IGF-1R specifically inhibits GHR, but not prolactin receptor signaling. GHR extracellular subdomain 2 is required, but not sufficient for sol IGF-1R action. These findings have implications for GH antagonist development.